Galois Group at Each Point for Some Self-Dual Curves. (30th January 2013) - Hayashi, Hiroyuki; Yoshihara, Hisao
Abstract : We study the Galois group defined by a point projection for plane curve. First, we present a sufficient condition that the group is primitive and then determine the structure at each point for some self-dual curves.